1984
DOI: 10.1093/nar/12.8.3695
|View full text |Cite
|
Sign up to set email alerts
|

Butylphenyl dGTP: a selective and potent inhibitor of mammalian DNA polymerase alpha

Abstract: BuPdGTP , the 2'-deoxyribonucleoside 5'-triphosphate of the DNA polymerase alpha (pol alpha)-specific inhibitor, N2-(p-n- butylphenyl )guanine, was examined with respect to its mechanism and its capacity to inhibit the mammalian DNA polymerases, pol alpha, pol beta, and pol gamma. BuP dGTP was specifically inhibitory for pol alpha, with no discernible activity on pol beta and pol gamma. The potency of BuP dGTP is unprecedented, with an apparent Ki less than 10 nanomolar. The unusual potency of the BuP dGTP is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 12 publications
4
41
0
Order By: Relevance
“…BuPdGTP is a GTP analog synthesized by Wright and Dudycz (68). Subsequent studies by them and others demonstrated that this chemical can inhibit the activity of purified DNA polymerase a, including the one from Xenopus laevis, at concentrations much lower than that needed to inhibit purified DNA polymerase 8 (11,33,40,68). It is difficult and may even be erroneous to apply data obtained in vitro with purified enzymes to the in vivo situation and determine which species of DNA polymerase operates in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…BuPdGTP is a GTP analog synthesized by Wright and Dudycz (68). Subsequent studies by them and others demonstrated that this chemical can inhibit the activity of purified DNA polymerase a, including the one from Xenopus laevis, at concentrations much lower than that needed to inhibit purified DNA polymerase 8 (11,33,40,68). It is difficult and may even be erroneous to apply data obtained in vitro with purified enzymes to the in vivo situation and determine which species of DNA polymerase operates in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…For the docking studies the dTTP ligand from the model complex was changed against a set of known nucleoside triphosphate inhibitors [13,14] and the non-nucleoside inhibitor aphidicolin [15]. The inhibitor molecules (all nucleosides contained a thymine base in order to get a correct Watson-Crick base pairing with the given template) were docked manually into the active site by superimposing the structures with the natural substrate in a conformation close to the dTTP template.…”
Section: Methodsmentioning
confidence: 99%
“…It exploits the facts that the two enzymes can be discriminated with a monoclonal antibody and a variety of specific inhibitors: First, the pol t~ specific monoclonal antibody 132-20 [10] neutralizes pol a completely but not pol t~ [11]; second, aphidicolin inhibits both pol d and pol tr and therefore permits detection of interfering pol/~ and/or pol ~,, if present, both completely resistant to this compound; third, the two deoxyribonucleoside triphosphate analogues BuPdGTP [8] and BuAdATP [9] are specific inhibitors of pol tr and are more than 1000-fold less effective against pol d [17]. Poly(dA)/oligo(dT)le-18 was used as the template, which is efficient for pol t~ [18] as well as for pol t~.…”
Section: Resultsmentioning
confidence: 99%
“…The pol ot specific inhibitors BuPdGTP [8] and BuAdATP [9] were used at concentrations that inhibited >98o70 of pol ~ (5/~M) and the pol ~ and d specific inhibitor aphidicolin at 50/~g/ml, resulting in inhibition of >95°70. The neutralizing monoclonal antibody 132-20 [10] specific for pol ot [11] was used in excess in an amount of 2.85/~g per assay.…”
Section: Methodsmentioning
confidence: 99%